2023
DOI: 10.1038/s41586-023-06362-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune sensing of food allergens promotes avoidance behaviour

Abstract: In addition to its canonical function of protection from pathogens, the immune system can also alter behaviour1,2. The scope and mechanisms of behavioural modifications by the immune system are not yet well understood. Here, using mouse models of food allergy, we show that allergic sensitization drives antigen-specific avoidance behaviour. Allergen ingestion activates brain areas involved in the response to aversive stimuli, including the nucleus of tractus solitarius, parabrachial nucleus and central amygdala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…These signals had not observed previously in vagal or sensory neuron input to the PBN. 12 This pathway is similar to that of paired taste conditioning, which involves GDF15 activation of brainstem neurons that signal the PBN. 16 Human urinary excretion of LTE4, which reflects the total tissue level, is 148 ± 58 ng/day (mean ± SD) in normal subjects and 189 ± 76 ng/day in diverse asthma patients, which is only marginally significantly higher than in normal subjects with considerable overlap.…”
Section: Leukotriene Mediation Of Avoidance Behaviormentioning
confidence: 89%
See 3 more Smart Citations
“…These signals had not observed previously in vagal or sensory neuron input to the PBN. 12 This pathway is similar to that of paired taste conditioning, which involves GDF15 activation of brainstem neurons that signal the PBN. 16 Human urinary excretion of LTE4, which reflects the total tissue level, is 148 ± 58 ng/day (mean ± SD) in normal subjects and 189 ± 76 ng/day in diverse asthma patients, which is only marginally significantly higher than in normal subjects with considerable overlap.…”
Section: Leukotriene Mediation Of Avoidance Behaviormentioning
confidence: 89%
“…Mice were immunized with ovalbumin (OVA) egg white protein in alum gel that evokes high concentrations of anti-OVA IgE antibody. 12,13 After drinking OVA water, OVA-allergic but not controlled mice developed allergic inflammation in the stomach and small intestines with diarrhea. OVA-allergic and control mice were then offered drinking water without and with OVA.…”
Section: Leukotriene Mediation Of Avoidance Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting example for food preference decisions beyond taste and hedonic value is immune sensing of food allergens (Florsheim et al, 2023). Studies have shown that humans suffering from food allergies-sometimes mismatched with "picky eaters"learn to make food preference or aversion decisions to avoid the intake of allergens being harmful to their health (Plum et al, 2023;Rothenberg, 2023).…”
Section: Food Preference Enigmasmentioning
confidence: 99%